Hybrid PSf/TNT-SO3H Ultrafiltration Membrane Fouling by Sodium Alginate: Effect of Permeation Flux on Fouling Resistance and Desalination Efficiency - Ibrahim Hotan Alsohaimi (Adsorption Science & Technology)
The development of low fouling UF membranes with boosting water flux for implementations in water purifications is critical. Organic foulants and ionic strength are the main characteristics of surface water which affect the membrane performance for water generation and seawater desalination. Low fouling hybrid ultrafiltration membranes were fabricated from a combination of sulfonic acid functionalized titanium nanotubes (TNTs-SO3H) and polysulfone (PSf) by the nonsolvent-induced phase separation approach. The membrane fouling was explored utilizing a polysaccharide sodium alginate (SA) as a hydrophilic nature organic matter, and the impact of Na+ and Ca2+ ions on alginate membrane fouling were also addressed. The results showed that the membranes’ water permeability and natural organic matter fouling resistances were affected by the proportion of TNTs-SO3H in the membranes. The inclusion of TNTs-SO3H improves the water penetration fluxes (Jw1) and surface hydrophilicity of the manufactured membranes. In the UF of sodium alginate solution, the produced membrane comprising 5% TNTs-SO3H exhibits a higher penetration flux and rejection value than the other membranes. The introduction of Na+ and Ca2+ ions to the SA solution reduces the membrane fouling. Furthermore, the adsorption investigation of sodium alginate solutions at pH=7 was lowered as the amount of TNTs-SO3H was increased. After ultrafiltration, the fouled membrane containing 5% TNTs-SO3H is readily removed, and recurrent antifouling experiments indicate a consistent and maximum filtration efficiency.